Réponses

2013-05-30T13:58:23+02:00

1. a) ( x+4 ) ( x-6 ) = x² + 6x * 4x - 24 = x² + 24x - 24

 

     b) ( -1+x ) ( x-2 ) = -1x + (-1) + 2 * x² - 2x = -3x + 1 + x²

 

2. x = 0 

 

    a) ( x+4 ) ( x-6) = ( 0+4 ) ( 0-6 ) = 4*6 = 24

 

    b) ( -1+x ) ( x-2 ) = ( -1+0 ) ( 0-2 ) = -1* 2 = -2

 

    x = 1

 

    a) ( x+4 ) ( x-6 ) = ( 1+4 ) ( 1-6 ) = 5*(-5) = -25

 

    b) ( -1+x ) ( x-2 ) = ( -1+1 ) ( 1-2 )  = 0 * (-1) = 0

 

J'espère t'avoir aidé ! :)

  • Utilisateur Brainly
2013-05-30T14:41:50+02:00

1) (x+2)(x+3)

    =x²+5x+6

 

(x+5)(x+7)

=x²+12x+35

 

(x+4)(x-6)

=x²-2x-24

 

(x-1)(x-2)

=x²-3x+2

 

2) (x+2)(x+3)=0

donc x=-2 ou x=-3

 

(x+5)(x+7)=0

donc x=-5 ou x=-7

 

(x+4)(x-6)=0

donc x=-4 ou x=6

 

(x-1)(x-2)=0

donc x=1 ou x=2